(untitled) (Research, Society and Development, 2022)
Objective: To explore the data available in the literature on breastfeeding and breastfeeding in infants with heart disease. Methodology: Integrative literature review, searching the SCIELO and PUBMED databases. The inclusion criteria adopted were: belonging to the time frame of the last 5 years, 2017 to 2021, being described in Portuguese, English or Spanish, with full text available. The exclusion criteria were: dealing with the result or effect of surgeries under the specific heart disease in question, editorials, monographs, texts and non-scientific content. Results: 23 studies were selected. Breastfeeding is the most effective option for NB/infant nutrition, as well as a predictor of infection prevention and reduction in NICU length of stay. Infants with heart disease are more susceptible to dysphagia, malnutrition, infections, and early weaning. Conclusion: Health education about the nutritional and immunological properties of breast milk, which are fundamental for reducing the risk of infection, for pre-surgical preparation, as well as for post-surgical recovery, is a very important care for the binomial. The early stimulation of breastfeeding must respect the newborn’s clinical condition. The understanding of the team about the importance of the notification of cases of congenital heart disease and the specificities of breastfeeding in babies with heart disease is necessary, so that caregivers are encouraged to invest in breastfeeding and are guided about the risks involved in this process, how to recognize them, and what attitudes to take if intervention is needed.